If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + x = -12 + 9 Combine like terms: -12 + 9 = -3 6 + x = -3 Solving 6 + x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + x = -3 + -6 x = -3 + -6 Combine like terms: -3 + -6 = -9 x = -9 Simplifying x = -9
| 2(5x+7)=30+3y+10 | | 2x+3y=25000 | | 1/12y-4=-8 | | 5f-3+6-7f= | | 9x+22=16x-27 | | (-3x)+8=1-(4x) | | 24=-6b-2b | | 64*x*2-8=41 | | 12(6-1/2x)=240 | | f(7pi/6) | | h-15=4 | | 6k-7+5k= | | 8(3b+2)=-30 | | http://opt-prod.s3.amazonaws.com/traject/files/item_attachments/relateds/000/429/917/original/Equation_6.PNG?1463559659 | | -6=-7x+8x | | 7.32=0.05-.18 | | f=7*32 | | 25*x*2+2=3 | | .3=0.300 | | 5n^2+1=126 | | 60+70+h=410 | | 3(8-2x)=60 | | 4(1+-12y)-3y=1 | | x*2-7=29 | | 2z(2z+7)-30=0 | | 6S-s= | | 129-43=12 | | 5.75+4.50(k-5)=26.25 | | 4b-11=1-2(3-b) | | 97=28*8+x | | 1.5*0=x-3 | | 14+16=-5(5x-6) |